Plan de gestión de calidad para la rehabilitación del Proyecto Hidroeléctrico de Tacares - Cháves-Murillo, Andrés (Instituto Tecnológico de Costa Rica, 2012)
La Práctica Profesional Dirigida fue realizada en la Empresa de Servicios Públicos de Heredia S.A, esta consistió en realizar un plan de gestión de calidad en la rehabilitación del Proyecto Hidroeléctrico de Tacares. Este se basa en la Guía de los Fundamentos para la Dirección de Proyectos, documento fundamental del Project Management Institute, así como de aspectos establecidos en la norma ISO 9001-2008 (International Organization for Standardization), en la cual se especifican los requisitos para un sistema de gestión de la calidad The Directed Professional Practice was developed in the Empresa de Servicios Públicos de Heredia S.A, and it consisted in a quality management plan in the rehabilitation of the Proyecto Hidroeléctrico de Tacares. This is based by Guide to the Project Management Body of Knowledge (PMBOK® Guide) - fourth edition, document of the Project Management Institute, also was used the International Organization for Standardization ISO 9001-2008 standard. The objectives of this report are: determine the actual process about the quality management, define inputs requested for planning, monitoring and controlling the quality for this project, analyze and suggest some tools for planning, monitoring and controlling the quality, define clearly the sequence and links of each of the results of the successors procedures of the quality management and develop the quality management plan for the rehabilitation of hydroelectric projects. This repost contain procedures, form and different tools, provides to the company, to establish a quality control process in all the construction project of the ESPH S.A.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2012.
Keywords: PMI; Hidroelectricidad; ISO 9001-2008; Dirección de proyectos; Listas de control